Cover Feature: Influence of the Electrolyte Salt Concentration on the Rate Capability of Ultra‐Thick NCM 622 Electrodes (Batteries & Supercaps 11/2020). Issue 11 (14th October 2020) - Kremer, Lea Sophie; Danner, Timo; Hein, Simon; Hoffmann, Alice; Prifling, Benedikt; Schmidt, Volker; Latz, Arnulf; Wohlfahrt‐Mehrens, Margret
Abstract : The Cover Feature illustrates the significant increase in energy density of ultra‐thick electrodes by the addition of LiPF6 salt. Optimizing the electrolyte salt concentration results in a mitigation of Li‐ion depletion occurring when ultra‐thick electrodes are discharged at high current densities. Microstructure resolved simulations confirm that the elevated charge carrier density allows activating larger parts of the thick electrode before transport limitations take over. More information about this collaborative study of three institutes located in the "Science City Ulm" can be found in the Article by A. Hoffmann and co‐workers .